Millennial money : how young investors can build a fortune - O'Shaughnessy, Patrick, 1985- (Palgrave Macmillan, 2014)
"Fact: the Millennial Generation will not be able to rely on pensions and social security in retirement. Instead, they will have to save and invest in the global stock market to meet their goals. When it comes to thinking about money, Millennials are, as a generation, different from their parents. They are skeptical of expert advice, yet more committed than baby boomers to passing wealth on to future generations. To build wealth, young people must start investing early and buck conventional market wisdom. Millennial Money will explain the most common mistakes that hurt investors' long-term returns and show why their investments in popular stocks or the hottest industry of the day have resulted in such underwhelming results. More importantly, the book will introduce a strategy that can help us overcome our shortcomings as investors. Armed with this strategy, Millennials can become the most successful investing generation in history"--